Evaluation of anti-estrogenic or estrogenic activities of aqueous root extracts of Gunnera manicata L. - Kristiane de Cássia Mariotti; Gabriela Cristina Schmitt; Fabiano Barreto; Rodrigo E. Fortunato; Rodrigo B. Singer; Eliane Dallegrave; Mirna Bainy Leal; Renata Pereira Limberger (Universidade de São Paulo, 2011)
Gunnera perpensa (Gunneraceae) is an African plant widely used in traditional medicine. This species is known for its activity involving the female reproductive system, such as inducing or increasing labor, treating female infertility, expelling the placenta and/or preventing post-partum hemorrhage. These properties are probably due to (z)-venusol, a majoritary compound, and its action in conjunction with substances in the whole extract and other natural products. In southern Brazil, a native species Gunnera manicata L. that also belongs to Gunneraceae can be found. In spite of the traditional use of G. perpensa, there is no pharmacological and phytochemical information regarding the South American Gunnera species. Therefore, the aim of this study was to investigate the activity of Brazilian G. manicata aqueous extracts on the reproductive system of immature female Wistar rats through a uterotrophic assay and to verify the presence of (z)-venusol by liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS). Data were analyzed by analysis of variance (ANOVA) and Bonferroni´s post-hoc test (p< 0.01). Results obtained shown that G. manicata extracts did not present in vivo anti or estrogenic activity. Furthermore, (z)-venusol compound was not found. This study represents the first preliminary screening done on the South American G. manicata species. Gunnera perpensa (Gunneraceae) é uma planta de origem africana extensamente utilizada na medicina tradicional do país. Esta espécie é conhecida por suas atividades no sistema reprodutor feminino, como indução ou aumento do trabalho de parto, tratamento da infertilidade em mulheres, expulsão da placenta e/ou impedimento de hemorragia pós-parto. Tais atividades devem-se, provavelmente, ao sinergismo existente entre o (z)-venusol, composto majoritário, e outros compostos presentes na planta. No sul do Brasil, encontra-se uma espécie nativa, Gunnera manicata L., pertencente à família Gunneraceae. Apesar do uso tradicional de G. perpensa, não há informações farmacológicas e fitoquímicas a respeito da espécie sul Americana de Gunnera. Assim, o objetivo deste estudo foi investigar a atividade de extratos aquosos da espécie brasileira G. manicata no sistema reprodutor de ratas Wistar imaturas através de ensaio uterotrófico e verificar a presença do composto (z)-venusol utilizando-se cromatografia líquida acoplada a espectrômetro de massas em tandem (CL-EM/EM). Para a análise estatística, utilizou-se ANOVA/Bonferroni (p<0,01). Os resultados obtidos demonstraram que os extratos de G. manicata testados não apresentaram atividade anti ou estrogênica in vivo. Na análise química não foi verificada a presença do composto (z)-venusol. Este estudo representa o primeiro screening realizado com a espécie sul-americana G. manicata.